The Australia Antigen
DOI: 10.1159/000391207
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis Associated Antigen and Periarteritis Nodosa (PAN)

Abstract: The detection of HAA was proved positive in 6 cases out of 7 histologically confirmed PAN.The presence of HAA does not necessarily depend on the evidence of hepatic manifestations. In those 7 cases were indeed observed 2 initial icteric hepatitis biologically and histologically proved, 4 transitory hepatomegalies, and in the last case (which was not the HAA negative one), no hepatic manifestation could be detected. It was possible to prove for at least 4 patients that they did not receive transfusions previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Though PAN was first described by Kussmaul and Maier in 1861, but the first description of its association with HBV was given by Tre'po et al and Gocke et al in 1970. [3][4][5] HCV positivity has occasionally been observed in patients with PAN, but it is not considered to be a major etiological factor; and is often observed concomitantly with other viral infections like HBV. [6][7][8] …”
Section: Polyarteritis Nodosa (Pan)mentioning
confidence: 99%
“…Though PAN was first described by Kussmaul and Maier in 1861, but the first description of its association with HBV was given by Tre'po et al and Gocke et al in 1970. [3][4][5] HCV positivity has occasionally been observed in patients with PAN, but it is not considered to be a major etiological factor; and is often observed concomitantly with other viral infections like HBV. [6][7][8] …”
Section: Polyarteritis Nodosa (Pan)mentioning
confidence: 99%
“…There are several diseases in which the frequency of HBsAg carriers is higher than in the general population or other diseases. These include chronic hepatitis (14), postnecrotic cirrhosis (15), primary hepatocellular carcinoma (PHC) (1 6), Down's syndrome (1 7), chronic renal disease treated with hemodialysis (18), some forms of leukemia (19), Hodgkin's disease (20), lepromatous leprosy (2 l), polyarteritis nodosa (22), and mixed cryoglobulinemia (23). For some of these, HBV is related to the etiology and/or pathogenesis; for others, abnormalities of the immune system are associated with an increased susceptibility to become a chronic carrier when exposed to the virus.…”
Section: Sex Differences In Response To Hepatitis B Virusmentioning
confidence: 99%
“…zeek described 5 different categories including 1) hypersensitivity angiitis, 2) allergic granulomatous arteritis as with asthma, 3) rheumatic arteritis involving the small arteries of the heart, 4) the classic periarteritis nodosa of Kussmaul and Maier, and 5) temporal or giant cell arteritis. Hepatitis B vasculitis has been described by several investigators in recent years, accounting for 30-40% ofall cases ofperiarteritis nodosa in some series (52), although others more recently suggested that only 8-10% were due to hepatitis (46). It appears to be the result of deposition ofimmune complex hepatitis B antigen and antibody directly in the tissue.…”
Section: Immunologic or Hypersensitivity Induced Arteritis In Manmentioning
confidence: 99%
“…Immune complex forms in the presence of excess viral antigen and these deposits in the arterial walls stimulate a lymphocytic response. This condition has been compared to the situation in hepatitis B,-associated arteritis in man (52).…”
Section: Immunologic or Hypersensitivity Induced Arteritis In Animalsmentioning
confidence: 99%